2000
DOI: 10.1080/000164700317393321
|View full text |Cite
|
Sign up to set email alerts
|

The Norwegian Arthroplasty Register: 11 years and 73,000 arthroplasties

Abstract: In 1985, the Norwegian Orthopaedic Association decided to establish a national hip register, and the Norwegian Arthroplasty Register was started in 1987. In January 1994, it was extended to include all artificial joints. The main purpose of the register is to detect inferior results of implants as early as possible. All hospitals participate, and the orthopedic surgeons are supposed to report all primary operations and all revisions. Using the patient's unique national social security number, the revision can … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
253
6
17

Year Published

2002
2002
2014
2014

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 461 publications
(291 citation statements)
references
References 27 publications
12
253
6
17
Order By: Relevance
“…loosening as much as 7% at midterm followup has been reported (Table 3) [1,11,20,28,41]. Distally supported prostheses have been introduced to increase initial and long-term stability [22,39] but may increase the risk of proximal osteopenia [46], whereas proximally fitting designs may lead to subsidence and early loosening [37,46].…”
Section: Discussionmentioning
confidence: 99%
“…loosening as much as 7% at midterm followup has been reported (Table 3) [1,11,20,28,41]. Distally supported prostheses have been introduced to increase initial and long-term stability [22,39] but may increase the risk of proximal osteopenia [46], whereas proximally fitting designs may lead to subsidence and early loosening [37,46].…”
Section: Discussionmentioning
confidence: 99%
“…Data concerning the identity of the patient, the diagnosis (indication), the date of surgery, whether the operation was primary or a revision, the cause of revision, the type of prosthesis, whether bone cement was used and the type of cement, the use of thrombosis prophylaxis, and antibiotics were registered in a form filled in by the operating surgeon (2,25). Using the unique identification number assigned to each resident of Norway, information from revision procedures involving exchange or removal of implants was linked to the corresponding primary operation.…”
Section: Methodsmentioning
confidence: 99%
“…The Scandinavian arthroplasty registers have shown that 3-15% of all prosthetic joint replacements in the hips and knees were done in RA patients (1)(2)(3)(4)(5)(6)(7). Replacements of other joints (e.g., elbows, wrists, fingers, and ankles) are predominantly performed in RA patients.…”
Section: Introductionmentioning
confidence: 99%
“…For nearly 50 years, THA has been one of the most effective and economical interventions in orthopaedic surgery [5,10,19] having a perioperative mortality rate usually less than 1% [2,3,6,8,23,[26][27][28][29]37]. Emerging demographic and epidemiologic studies are projecting large increases in the demand for primary and revision arthroplasty over the next two decades [14][15][16].…”
Section: Introductionmentioning
confidence: 99%